Stirred Yogurt as a Delivery Matrix for Freeze-Dried Microcapsules of Synbiotic EVOO Nanoemulsion and Nanocomposite - El-Sayed, Hoda S.; Youssef, Khamis; Hashim, Ayat F. (Frontiers in Microbiology, 2022)
Nowadays, dairy products are considered a good matrix to deliver many functional substances either vital oils or probiotic cells. Two models of microcapsules were produced from co-encapsulation of extra virgin olive oil (EVOO) nanoemulsion or nanocomposite and synbiotic bacteria (maltodextrin with Lactobacillus acidophilus and Bifidobacterium bifidum) using the freeze-drying technique. These models of microcapsules were added to stirred yogurt and then its storage effect on microbiology, chemically, and sensory properties were evaluated during 21 days. The average droplet size and zeta potential distribution of EVOO nanoemulsion and nanocomposite were investigated. Also, oxidative stability, microencapsulation efficiency, release profile, and antioxidant activity were studied. The results showed that the average particle size of EVOO nanoemulsion and nanocomposite ranged between 416 and 475 nm while zeta potential was -39.6 and -33.6 mV, respectively. The induction period of EVOO extracted from nanoemulsion and nanocomposite microcapsules models were 11.30 and 8 h. The microencapsulation efficiency of probiotic and EVOO was determined at 88.84 and 65.61 % for the nanoemulsion microcapsules model, while the nanocomposite microcapsules model showed 98.49 and 72%. The two models of microcapsules have boosted the viability of probiotic bacteria inside stirred yogurt than free cells. Also, the presence of microcapsules didn’t affect the viability of stirred yogurt starter cultures, and the high values for the total solid and protein were detected. Therefore, the results recommended that stirred yogurt is a good delivery carrier for highly antioxidant and healthy microcapsules of synbiotic EVOO nanoemulsion and nanocomposite.